A prática e o conhecimento sobre educação ambiental dos alunos do ensino fundamental da Escola Estadual Jose Ometto - Dalge, Silviane Maria Magdalon (2015)
This work was subject to environmental education, specifically the trash because, increasingly, the waste is inevitable, we live in a consumer society where we buy things we do not need and discard others without any conscience, do not stop to think about what really need to simply discard and discard increasingly., is the result of this is the environmental degradation and depletion of natural resources, the main objective was to demonstrate the importance of environmental education in science teaching and discuss what contributions of schools in environmental awareness training among children and young people, knowing that issues related to the environment, covering environmental education, separate collection, recycling biodiversity, directly affect all social and environmental issues, developed a job with students of the 7th anniversary of the State School Jose Ometto, seeking to deepen and clarify such issues, given that the students of this school are from different parts of the city and experience different situations.